Accurate Estimation of Drug Intake Day by Microsegmental Analysis of a Strand of Hair by Use of Internal Temporal Markers. (15th January 2020) - Kuwayama, Kenji; Nariai, Maika; Miyaguchi, Hajime; Iwata, Yuko T; Kanamori, Tatsuyuki; Tsujikawa, Kenji; Yamamuro, Tadashi; Segawa, Hiroki; Abe, Hiroko; Iwase, Hirotaro; Inoue, Hiroyuki
Abstract: Background: Segmental hair analysis can be useful for estimating the time of drug intake. However, this estimation is currently only accurate to within several months. We previously conducted microsegmental analysis of a strand of hair to visualize drug distribution at a spatial resolution of 0.4 mm, which corresponds to daily hair-growth length. Herein, we describe a procedure for accurately estimating the day of drug intake by using internal temporal markers (ITMs) to mark a timescale in the analyzed strand of hair. Methods: Five drugs were administered in a single dose to the subjects, and then administration was stopped for several weeks. Two subsequent cycles of drug administration and similar withdrawal were performed. For analysis, a strand of hair was plucked from the subject's scalp. The first intake day was considered as the unknown and the drugs administered second and third were regarded as the ITMs. The first intake day was estimated based on the distance from hair root end to 3 drug peaks and 3 known days (hair sampling and 2 ITM cycles). Results: The drug concentration–hair segment curve had 3 peaks, which reflected the 3 drug cycles. The use of ITMs reduced the error of the true intake day to within 2 days, because the growth rate of the analyzed strand of hair was accounted for by the 2 ITMs. Conclusions: The estimated accuracy showed little dependency on drug and individual variation. This procedure for estimating the time of drug intake down to a particular day can be used in drug-related crimes, drug abuse and compliance, and for medical diagnosis.